Minhas veredas: experiências contributivas para a formação colaborativa de gestores escolares - Mapeli, Desiclei Mara de Oliveira Barrocal (2023)
This research deals with the training of school managers. It is about presenting my researcher narrative, from the perspective of my managerial practice over the years of work, in reflection on what was developed: my actions, contexts, schools, professionals, projects developed countries and communities. The most general question that arises is: How does the training process of this researcher take place as the subject and object of this investigation in the perspective of her professional trajectory as an educational manager of a municipality in the ABC region of São Paulo? Based on this question, the collaborative training of managers was defined as the focus of the research, from the point of view of practice, in dialogue with the authors, inquiring about the concepts. The general objective of this research is to understand how my training as a researcher/researched and manager has taken place, in my work with the managers, whom I follow. As specific research objectives, the following are presented: a) To describe and analyze my school, initial and academic training considering its implications in professional practice as a school principal; b) Describe and analyze my professional performance as an educational service coordinator in a municipality in the ABC region of São Paulo; c) Analyze the continuing education of school managers considering the perspectives of collaborative training practices; d) Elaborate a proposal for training school managers with a focus on professional development and collaborative work. Using autoethnography as a methodological path of analysis, the empirical research involves my narrative as a researcher about my professional trajectory throughout my professional career and in my work with managers. The process of collecting information began with the use of the memory of my own experiences, recorded in field notebooks, photographs, conversations and reports. Through memories, writing, reflection, it allowed me to see the points in common in this trajectory, what was constituted, in relation to all these factors, in an exercise that allowed the analysis of my constitution as a manager. Working with 15 managers of five schools in a municipal education network in the ABC region of São Paulo provided data on my current management, in dialogue with the entire journey I've already taken and with the authors I've read as a theoretical reference, which helped to re-signify my practice. The study reveals that managers bring the practice of exchanging information with each other, about their professional knowledge acquired throughout their careers and that the absence is not related to the lack of information exchange between managers, but in relation to institutionalized spaces and structured for a collaborative and continuous training of managers that provide listening, dialogue and propositions with a view to solutions for work situations, based on problematization and training centered on the school. Considering that the main concern of the school should be the promotion of quality education, the complexity of the role of managers puts them in front of issues that they need to face in the school routine, therefore, the learning relationships conceived in collaborative training help in the development of solutions creative, enabling change; therefore, it is essential that they are adequately prepared and supported.